The Architectural Characteristics Linkage of Rumah Gadang in the West Coast and South Solok with the Rumah Gadang in the Luhak Nan Tigo and its Rantau - Muhammar Khamdevi (Universitas Medan Area, 2021)
The Pesisir Barat, Solok, and Solok Selatan areas are the rantau (vassal) of the Pagaruyung Kingdom after the withdrawal of the Malayupura Kingdom and the Malacca Sultanate, namely the Inderapura Kingdom in the 15th century and the Sungai Pagu Kingdom in the 16th century. At a glance, the Rumah Gadang in the Pesisir Barat area are similar to the Rumah Gedang in Batanghari Hulu and the Rumah Godang in Batang Kuantan. Meanwhile, the Rumah Gadang in Solok and Solok Selatan seem to have all the Rumah Gadang collections in the Luhak Nan Tigo area (Tanah Datar, Agam, and Limapuluh Koto). Therefore, this study tries to explore the relationship between the characteristics of traditional houses in these areas. This research method is qualitative, by conducting literature reviews, field studies, and analyzing the architecture and comparing it with traditional houses in these areas to get a more comprehensive conclusion. The results of this study indicate that there is a general relationship between the characteristics of the Rumah Gadang in the West Coast, Solok, and South Solok with the Rumah Gadang in the Luhak Nan Tigo area.